INSTITUTIONAL DEVELOPMENT MODEL OF URBAN WASTE MANAGEMENT (Survey in Bogor Waste Management) - Samsuri, Samsuri; Maulana, Lucky Hikmat (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Generally, waste management in major cities in Indonesia are still relying on landfilling that requiring large land and continue to grow along with the increasing volume of waste generation from day to day. Meanwhile the land where the final disposal (landfill) of waste in large cities increasingly limited. This study aims to develop a model of waste management through waste reduction, ranging from the source. There are several criteria and sub-criteria that should be considered in developing a model that negative impacts arising can be minimized.Based on the results of previous studies, using Analytical Network Process (ANP), the chosen model for the handling of waste is individual models on a scale of RT/RW. In order to implement this model required an appropriate institutional because it involves community participation as the key to success. By using Â Interpretive Structural Modeling (ISM) showed that the treatment of urban waste must be oriented on raising awareness of the public to maintain cleanliness and environmental health through the concept of 3R (reduce, reuse and recycle). To overcome the obstacles faced during the Local Government should need to restructure the organization of waste management by establishing a Public Service Board/BLUD business Waste and Waste ManagementCommissionoftheCity/KPSK.KEYWORDSVolume of waste generation, Public Service Board